Peer-support: a coping strategy for nurses working at the Emergency Ambulance Service - Carvello, Maicol; Zanotti, Filippo; Rubbi, Ivan; Bacchetti, Silvia; Artioli, Giovanna; Bonacaro, Antonio (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the study: Working in the emergency medical service often exposes nurses to highly stressful situations and can impact their quality of life. Among the strategies aimed at mitigating the effects of this phenomenon, peer-supporting represents an emerging model used in the emergency medical service setting. The aim of the study is to explore the experiences, the opinions and feelings of emergency medical service nursing staff in relation to the use of the peer supporting model. Methods: A semi-structured interview was carried out. Participants were recruited on a voluntary basis from an emergency medical service in the north of Italy. Interviews were audio-recorded and the data extracted were anonymised. Results: 14 nurses participated in the study. The totality of the participants recognized that their daily clinical practice, especially when involving paediatric patients, can have a profound emotional impact on their life in general. Furthermore, interviewees admitted that their personal copying mechanisms did not seem to be entirely effective when processing their painful experiences.  The majority of the participants were in favour of introducing a peer-supporter in the ambulance service. Conclusions: This study emphasises the need to implement emotional support tools for non-hospital emergency nurses in daily clinical practice, in order to facilitate emotional decompression secondary to particularly stressful interventions as soon as possible. The peer-supporting strategy could represent, in this direction, a valid and shared model.